Molecular identification and pathogenicity of 'Rhizoctonia' spp. recovered from seed and soil samples of the main bean growing area of Argentina - Spedaletti, Yamila Andrea (2017)
The objective of this study was to perform the molecular and pathogenic characterization of Rhizoctonia solani in bean seed and soil samples from fields with root rot symptoms in northwestern Argentina. Fifty-two Rhizoctonia spp. isolates were collected in ten naturally infested bean fields and characterized by morphological traits, DNA sequencing, and pathogenicity. The mycelium color, the pattern of sclerotia formation, and the number of nuclei per hyphal cell were determined for each isolate. According to the variability in the rDNA-ITS region, isolates were identified as R. solani (85%), Waitea circinata var. zeae (Rhizoctonia zeae) (2%) and Rhizoctonia spp. (13%). Most isolates of R. solani (92%) were found to belong to the anastomosis group (AG) AG 4, including seven AG 4 HG-I and nine AG 4 HG-III isolates. AGs obtained from soil samples were more variable than those obtained from seed samples. Molecular identification of the isolates was in agreement with their morphological characterization. In addition, aggressiveness of the isolates towards bean seedlings was assessed in the greenhouse. Four virulence categories were defined according to the disease reaction on root and foliar tissues, which showed great variability in virulence among the isolates. Our results suggest that both seed and soil-borne inoculum may play a significant role in pathogen dispersal in the region. This is the first study on Rhizoctonia species and AGs in bean seed and soil in this region and it may contribute towards an efficient control strategy for bean diseases caused by Rhizoctonia species.